A gel electrolyte for lithium-sulfur battery and preparation method thereof

By using specific lithium salts and ether solvents in lithium sulfur batteries, combined with leucine as an initiator, gel electrolyte is prepared, which solves the problems of dissolution loss and shuttle effects of active substances in lithium sulfur batteries, and significantly improves the electrochemical performance and safety of the battery.

CN118507821BActive Publication Date: 2025-03-07贵州轻工职业大学
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410622768.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-03-07
Estimated Expiration
2044-05-20

AI Technical Summary

Technical Problem

When lithium-sulfur batteries are circulated in traditional liquid ether electrolytes, the dissolution loss and shuttle effects of active substances are severe, resulting in poor battery circulation stability, reduced Coulomb efficiency and increased safety risks.

Method used

Lithium bistrifluoromethanesulfonimide and lithium nitrate were used as lithium salts, mixed solvents of 1,3-dioxolane and ethylene glycol dimethyl ether were used as ether solvents, and leucine as initiator. Gel electrolytes were prepared in situ by a one-step method to inhibit the dissolution loss of active substances and the shuttle effect.

Benefits of technology

It significantly improves the electrochemical performance of lithium-sulfur batteries, including cycle stability and Coulomb efficiency, reduces self-discharge and lithium negative electrode corrosion, and improves the safety factor of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118507821B_ABST
    Figure CN118507821B_ABST
Patent Text Reader

Abstract

The present invention discloses a gel electrolyte for lithium-sulfur battery and a preparation method thereof. The present invention adopts lithium bis(trifluoromethanesulfonyl imide) and lithium nitrate as lithium salts, a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether as an ether solvent, and leucine as an initiator. The initiator is added to a basic liquid ether electrolyte composed of the above lithium salt and ether solvent, and the gel electrolyte is prepared in situ at room temperature by a one-step method. The experimental results show that the prepared gel electrolyte exhibits excellent electrochemical cycle stability and rate performance when applied to lithium-sulfur batteries. In addition, the preparation method of the present invention has a simple process, does not require ultraviolet irradiation, does not require high temperature and high pressure conditions, and does not involve the synthesis of complex materials. The entire preparation process does not generate polluting and toxic gases, meets environmental protection standards, is safe and controllable, and meets safety standards; it is easy to promote and apply industrialization, and therefore has broad development potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of battery materials and relates to a gel electrolyte for a lithium-sulfur battery and a preparation method thereof. Background Art

[0002] Lithium-sulfur batteries have attracted much attention from researchers due to their high theoretical energy density (2600Wh / kg) and theoretical specific capacity (1675mAh / g), as well as the intrinsic advantages of elemental sulfur such as low price, environmental friendliness and abundant reserves. They are considered to be one of the most promising next-generation energy storage secondary battery systems.

[0003] Traditional lithium-sulfur batteries use excessive amounts of liquid ether electrolytes, which have the following problems in actual use:

[0004] (1) When lithium-sulfur batteries circulate in ether electrolytes, they will generate lithium polysulfide, an intermediate product that is highly soluble in liquid electrolytes, causing the active material to be lost from the positive electrode side, resulting in poor battery cycle stability;

[0005] (2) During the charging process, the soluble long-chain lithium polysulfide generated on the positive electrode side will migrate through the diaphragm to the lithium negative electrode under the action of the concentration gradient, and react with metallic lithium to generate short-chain lithium polysulfide with a lower valence state; since the charge density of short-chain lithium polysulfide is higher, the influence of the electric field force is greater than the influence of the concentration gradient, and it will migrate back to the positive electrode side to regenerate long-chain lithium polysulfide, forming a shuttle effect. This effect will corrode the metallic lithium negative electrode, resulting in a decrease in the battery's coulombic efficiency and self-discharge behavior, thereby reducing the battery's cycle life. In severe cases, it may even cause the battery to be unable to reach the charge cut-off voltage, affecting its normal operation;

[0006] (3) Liquid ether electrolytes are prone to leakage and flammability, which will reduce the safety factor of lithium-sulfur batteries in practical scenarios and increase safety risks.

[0007] The existence of the above problems has greatly limited the commercial development and application of lithium-sulfur batteries. Therefore, it is urgent to develop a high-performance electrolyte for lithium-sulfur batteries. Summary of the invention

[0008] In view of the technical problems existing in the background technology, the purpose of the present invention is to provide a gel electrolyte for lithium-sulfur battery and a preparation method thereof. The gel electrolyte prepared by the present invention can better inhibit the dissolution and loss of active substances in lithium-sulfur batteries and alleviate the shuttle effect, thereby improving the electrochemical performance of lithium-sulfur batteries and also improving the safety factor of the battery.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions:

[0010] A first aspect of the present invention provides a method for preparing a gel electrolyte for a lithium-sulfur battery, comprising the following steps:

[0011] S1, adding lithium salt to an ether solvent, stirring and mixing, to obtain a mixed material A;

[0012] The ether solvent is a mixed solvent of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME); the lithium salt includes lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate (LiNO 3 );

[0013] S2. Add leucine as an initiator to the mixed material A, stir and react at room temperature, and let it stand to obtain a gel electrolyte for lithium-sulfur batteries.

[0014] Preferably, in the mixed solvent, the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:(0.5-1), and more preferably 1:1.

[0015] Preferably, in the mixed material A, the molar concentration of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is 0.5 to 2.0 mol / L, and more preferably 1.0 mol / L.

[0016] Preferably, in the mixed material A, the mass concentration of the lithium nitrate is 1-10wt%, more preferably 5wt%.

[0017] Preferably, in step S2, the amount of leucine added is 1.5-4.5wt% of the total mass of the mixed material A, and more preferably 2wt%.

[0018] Preferably, in step S2, the stirring reaction time is 3 to 8 hours, and the standing time is 8 to 12 hours.

[0019] The second aspect of the present invention provides a gel electrolyte for lithium-sulfur batteries prepared by the above preparation method.

[0020] A third aspect of the present invention provides a lithium-sulfur battery, comprising the above-mentioned gel electrolyte for lithium-sulfur battery.

[0021] The present invention has the following beneficial effects:

[0022] (1) The present invention uses lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate as lithium salts, a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether as an ether solvent, and leucine as an initiator. By adding the initiator to the basic liquid ether electrolyte composed of the above lithium salt and ether solvent, a gel electrolyte is prepared in situ at room temperature by a one-step method. Compared with conventional basic liquid ether electrolytes, the gel electrolyte prepared by the present invention can act as a barrier layer, reduce the dissolution and loss of active material lithium polysulfide, inhibit the shuttle effect, and further inhibit the corrosion of the lithium negative electrode, reduce the self-discharge of the battery, and thus achieve the improvement of the electrochemical performance of the battery.

[0023] (2) When the gel electrolyte prepared by the present invention is applied to a lithium-sulfur battery, it exhibits excellent cycle stability in an electrochemical performance test.

[0024] (3) The preparation method of the present invention has a simple process, does not require ultraviolet light irradiation, does not require high temperature conditions, and does not involve the synthesis of complex materials. The entire preparation process does not produce polluting and toxic gases, meets environmental protection standards and does not involve high temperature and high pressure reactions. It is safe and controllable and meets safety standards. It is easy to promote and apply industrially, and therefore has good commercial application prospects in the field of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 Optical images of the gel electrolytes ((b), (c)-(d)) prepared in Example 2 and Comparative Examples 2-3 and the basic electrolyte (a) prepared in Comparative Example 1;

[0027] Figure 2 The graph is a test result of the cycle stability at 0.1C when the gel electrolyte prepared in Example 2 and the basic electrolyte (control group) prepared in Comparative Example 1 are applied to lithium-sulfur batteries;

[0028] Figure 3 The time-voltage curve diagram of the gel electrolyte prepared in Example 2 and the basic electrolyte (control group) prepared in Comparative Example 1 when applied to a lithium-sulfur battery (used to test the self-discharge performance of the battery);

[0029] Figure 4 The graph is a test result of cycle stability at 0.5C when the gel electrolyte prepared in Example 2 and the basic electrolyte (control group) prepared in Comparative Example 1 are applied to lithium-sulfur batteries;

[0030] Figure 5 The FSEM image of the lithium negative electrode after the self-discharge test when the gel electrolyte prepared in Example 2 is applied to a lithium-sulfur battery;

[0031] Figure 6 This is the FSEM image of the lithium negative electrode after the self-discharge test when the basic electrolyte prepared in Comparative Example 1 is applied to a lithium-sulfur battery. DETAILED DESCRIPTION

[0032] In the following description, for the purpose of illustration rather than limitation, specific details such as specific system structures and technologies are provided to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may also be implemented in other embodiments without these specific details.

[0033] Example 1

[0034] 1,3-Dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:1 to obtain a mixed solvent, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate (LiNO 3 ) was added to the mixed solvent to make the molar concentration of LiTFSI 1.0 mol / L and LiNO 3 The mass concentration is 5wt%, and the mixture is stirred evenly to obtain a mixed material A; then 1.5wt% of leucine in the total mass of the mixed material A is added to the mixed material A, and the mixture is stirred for reaction at room temperature for 5h, and allowed to stand for 10h to obtain a gel electrolyte for a lithium-sulfur battery.

[0035] Example 2

[0036] 1,3-Dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:1 to obtain a mixed solvent, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate (LiNO 3 ) was added to the mixed solvent to make the molar concentration of LiTFSI 1.0 mol / L and LiNO 3 The mass concentration is 5wt%, and the mixture is stirred evenly to obtain a mixed material A; then, 2wt% of leucine is added to the mixed material A, and the mixture is stirred for reaction at room temperature for 5h, and allowed to stand for 10h to obtain a gel electrolyte for a lithium-sulfur battery.

[0037] Example 3

[0038] 1,3-Dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:1 to obtain a mixed solvent, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate were added to the mixed solvent to make the molar concentration of LiTFSI 1.0 mol / L and LiNO 3The mass concentration is 5wt%, and the mixture is stirred evenly to obtain a mixed material A; then 4.5wt% of leucine of the total mass of the mixed material A is added to the mixed material A, and the mixture is stirred for reaction at room temperature for 5h, and allowed to stand for 10h to obtain a gel electrolyte for a lithium-sulfur battery.

[0039] Example 4

[0040] 1,3-Dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:0.8 to obtain a mixed solvent, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate were added to the mixed solvent to make the molar concentration of LiTFSI 1.0 mol / L and LiNO 3 The mass concentration is 10wt%, and the mixture is stirred evenly to obtain a mixed material A; then 3wt% of leucine is added to the mixed material A, the mixture is stirred for reaction at room temperature for 12h, and the mixture is allowed to stand for 8h to obtain a gel electrolyte for a lithium-sulfur battery.

[0041] Example 5

[0042] 1,3-Dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:0.5 to obtain a mixed solvent, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate were added to the mixed solvent to make the molar concentration of LiTFSI 0.5 mol / L and LiNO 3 The mass concentration is 6wt%, and the mixture is stirred evenly to obtain a mixed material A; then 2wt% of leucine is added to the mixed material A, the mixture is stirred for reaction at room temperature for 8h, and the mixture is allowed to stand for 10h to obtain a gel electrolyte for a lithium-sulfur battery.

[0043] Example 6

[0044] 1,3-Dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:1 to obtain a mixed solvent, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate were added to the mixed solvent to make the molar concentration of LiTFSI 2.0 mol / L and LiNO 3 The mass concentration is 1wt%, and the mixture is stirred evenly to obtain a mixed material A; then 1.5wt% of leucine in the total mass of the mixed material A is added to the mixed material A, the mixture is stirred for reaction at room temperature for 3h, and the mixture is allowed to stand for 12h to obtain a gel electrolyte for a lithium-sulfur battery.

[0045] Comparative Example 1

[0046] 1,3-Dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:1 to obtain a mixed solvent, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate were added to the mixed solvent to make the molar concentration of LiTFSI 1.0 mol / L and LiNO 3 The mass concentration of the mixture was 5wt%, and the mixture was stirred evenly to obtain a mixed material A. The mixture was stirred at room temperature for 5 hours and allowed to stand for 10 hours to obtain a basic electrolyte (as a control group).

[0047] Comparative Example 2

[0048] 1,3-Dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:1 to obtain a mixed solvent, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate (LiNO 3 ) was added to the mixed solvent to make the molar concentration of LiTFSI 1.0 mol / L and LiNO 3 The mass concentration is 5wt%, and the mixture is stirred evenly to obtain a mixed material A; then 1wt% of leucine in the total mass of the mixed material A is added to the mixed material A, the mixture is stirred for reaction at room temperature for 5h, and the mixture is allowed to stand for 10h to obtain a gel electrolyte for a lithium-sulfur battery.

[0049] Comparative Example 3

[0050] 1,3-Dioxolane (DOL) and ethylene glycol dimethyl ether (DME) were mixed in a volume ratio of 1:1 to obtain a mixed solvent, and then lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate were added to the mixed solvent to make the molar concentration of LiTFSI 1.0 mol / L and LiNO 3 The mass concentration is 5wt%, and the mixture is stirred evenly to obtain a mixed material A; then, 5wt% of leucine of the total mass of the mixed material A is added to the mixed material A, and the mixture is stirred for reaction at room temperature for 5h, and allowed to stand for 10h to obtain a gel electrolyte for a lithium-sulfur battery.

[0051] 1. Optical characterization of the gel electrolyte for lithium-sulfur battery prepared in Example 2 and Comparative Examples 2-3 and the basic electrolyte prepared in Comparative Example 1 is shown in Figure 1 .

[0052] Figure 1The results show from a macroscopic perspective that the addition of leucine causes the original basic electrolyte to evolve from flow to gelation. When the initiator leucine is not added (0wt%), the obtained basic electrolyte (Comparative Example 1) shows obvious fluidity under both tilted and inverted conditions; the addition of leucine can cause polymerization reaction inside the electrolyte, but when the addition amount is only 1wt%, the degree of polymerization is still low, and it still shows obvious flow phenomenon under inverted and tilted states (Comparative Example 2); and when the addition amount is 2wt%, the obtained electrolyte (Example 2) can be clearly observed to have non-flowability under tilted and inverted conditions, indicating that polymerization occurs inside the electrolyte, and at the same time, a suitable degree of polymerization will benefit lithium ion transmission. However, when the addition amount is 5wt% (Comparative Example 3), although the electrolyte also shows a non-flowing state, its excessive degree of polymerization will be detrimental to ion transmission. Therefore, the addition amount of the initiator leucine should not be too low or too high, otherwise it will be detrimental to electrolyte gelation and battery performance.

[0053] 2. Effect of leucine dosage on conductivity and lithium ion transference number of gel electrolyte

[0054] The specific steps are as follows: all CR2032 button batteries are assembled in a glove box filled with argon, and the diaphragm soaked with electrolyte (prepared by Examples 1-3 and Comparative Examples 1-3) is placed between two stainless steel sheets to assemble a symmetrical battery. After the battery assembly is completed, it is left to stand for 24 hours, and then the electrochemical impedance of the battery is tested using an electrochemical workstation. The ionic conductivity is calculated by the following formula:

[0055]

[0056] Where, σ is the ionic conductivity, L is the thickness of the membrane, and R b is the bulk resistance obtained for the test battery, and A is the effective area.

[0057] Place the diaphragm soaked with enough electrolyte between two lithium sheets to assemble a symmetrical battery. After the battery is left to stand for 24 hours, use an electrochemical workstation to test the battery's interface impedance; then perform a constant potential polarization test, set the voltage to 10mV, and the polarization time to 1000 seconds; immediately after the polarization test, perform the battery impedance test again. The lithium ion migration number can be calculated using the following formula:

[0058]

[0059] in, is the lithium ion migration number, I 0 and I SS are the initial current and steady-state current during constant voltage polarization, R 0 and R SSare the interface impedances at the initial state and steady state, respectively, and ΔV is the applied polarization voltage. The experimental results are shown in Table 1.

[0060]

[0061] Note: Lithium ion conductivity = ion conductivity × lithium ion migration number

[0062] Combination Figure 1 From the optical photographs and the test results in Table 1, it can be seen that when the amount of leucine is 2wt% of the electrolyte mass (Example 2), the comprehensive performance of the prepared gel electrolyte is optimal, that is, the electrolyte is in a non-flowing gel state and the lithium ion conductivity is higher. From the results in Table 1, it can be seen that the electrolyte lithium ion conductivity will decrease with the increase in the amount of initiator leucine added. This is mainly because the increase in the amount of leucine will increase the degree of electrolyte gelation, which is not conducive to the ion conductivity of lithium ions. Therefore, after satisfying the electrolyte gelation, the amount of initiator leucine added should not be too high, otherwise it will be detrimental to the battery performance.

[0063] 3. The gel electrolyte prepared in Example 2 and the basic electrolyte (control group) prepared in Comparative Example 1 were used to prepare lithium-sulfur batteries. The specific steps of battery assembly were as follows:

[0064] Negative electrode sheet of the battery: lithium sheet is used as the negative electrode (thickness is 100μm and diameter is 14mm);

[0065] Positive electrode sheet of the battery: The preparation method is as follows: (a) sulfur powder and Ketjen black are weighed in a mass ratio of 7:3 and then ball-milled in a ball mill for 6 hours to obtain a primary mixture of sulfur and carbon; the obtained primary mixture is vacuum-sealed in a glass tube and then placed in an oven at 400°C for 10 hours, and after cooling to room temperature, a Ketjen black / sulfur composite material is obtained; (b) the obtained Ketjen black / sulfur composite material, carbon nanotubes, and LA133 are mixed in a mass ratio of 8:1:1, stirred for 6 hours, and a uniformly mixed slurry is obtained, and then the slurry is coated on a carbon-coated aluminum foil, and the aluminum foil is placed in an oven at 70°C for 10 hours, and the positive electrode material is obtained after drying; finally, a sheet puncher is used to cut the positive electrode material into small discs with a diameter of 8 mm for standby use.

[0066] Electrolyte: the gel electrolyte prepared in Example 2 or the basic electrolyte prepared in Comparative Example 1 (control group);

[0067] Diaphragm: Celagrd2400 (diameter 19 mm, thickness 7 μm); CR2032 (button type) lithium-sulfur battery was assembled in a glove box filled with argon. Electrochemical performance test of the assembled lithium-sulfur battery:

[0068] (1) Cycle stability at 0.1C rate: After the assembled lithium-sulfur battery was left at 25°C for 24 h, it was activated for 3 cycles at a rate of 0.05C between 1.7 and 2.8V, and then the cycle stability performance test was performed at a rate of 0.1C. The results are shown in Figure 2 ;

[0069] Depend on Figure 2 The results show that when the gel electrolyte prepared in Example 2 is used, the first cycle discharge capacity of the corresponding lithium-sulfur battery is 1178 mAh / g, the capacity after activation is 866 mAh / g, and after 95 cycles, the capacity is still 741 mAh / g (corresponding to a surface capacity of 5.2 mAh / cm 2 , which is higher than the surface capacity of 4mAh / cm required by commercial lithium-ion batteries 2 ); At the same time, during the entire cycle, the average coulombic efficiency of the lithium-sulfur battery remained at about 99.1%. On the contrary, when the basic electrolyte prepared in Comparative Example 1 (control group) was used, the corresponding lithium-sulfur battery had a first-cycle discharge capacity of up to 1200 mAh / g and a capacity of 817 mAh / g after activation. However, after 95 cycles, the capacity decreased to 414 mAh / g (corresponding to a surface capacity of 3.0 mAh / cm 2 ); at this time, the average coulombic efficiency of the battery in the entire cycle process is only 97.5%. The above results show that the gel electrolyte prepared in Example 2 of the present invention can effectively inhibit the dissolution of active material lithium polysulfide and control the shuttle effect when applied to lithium-sulfur batteries, so that the assembled lithium-sulfur battery has excellent cycle stability.

[0070] (2) Self-discharge performance: The assembled lithium-sulfur battery was left at 25°C for 24 hours, activated at a rate of 0.05C for 3 cycles between 1.7 and 2.8V, and then cycled at a rate of 0.1C for 7 cycles; then, after the lithium-sulfur battery was charged to 2.8V, the battery was left at rest for 72 hours (3 days) to observe the change in voltage with the rest time. The corresponding voltage value at the end of the rest period reflects the severity of the shuttle effect, and further reflects the degree of corrosion of lithium polysulfide on the metal lithium negative electrode. The results are shown in Figure 3 .

[0071] Depend on Figure 3 The results show that when the gel electrolyte prepared in Example 2 is used, the voltage of the battery is 2.21 V after 3 days of standing; when the control group electrolyte is used, the voltage of the battery is 2.18 V after 3 days of standing. This test result shows that the gel electrolyte prepared in Example 2 can effectively reduce the self-discharge of lithium-sulfur batteries, reduce the shuttle effect, inhibit the corrosion of the lithium negative electrode and protect the lithium negative electrode.

[0072] (3) Cycle stability at 0.5C rate: After the assembled lithium-sulfur battery was left at 25°C for 24 h, it was activated for 3 cycles at a rate of 0.05C between 1.7 and 2.8V. Then, the cycle stability performance test was performed at a rate of 0.5C. The results are shown in Table 1. Figure 4 ;

[0073] Depend on Figure 4 As can be seen from the results, at a high rate of 0.5C, the lithium-sulfur battery assembled using the gel electrolyte prepared in Example 2 has a discharge capacity of 723 mAh / g after 150 cycles, and the average coulombic efficiency of the battery is as high as 99.6% during the entire cycle. In contrast, the lithium-sulfur battery assembled using the basic electrolyte (control group) prepared in Comparative Example 1 has a specific capacity of only 543 mAh / g after 150 cycles, and the average coulombic efficiency of the battery is only 98.4% during the entire cycle. This test result shows that even at a higher rate, the gel electrolyte prepared in Example 2 can still effectively inhibit the dissolution of lithium polysulfide and enhance the cycle stability of the battery.

[0074] 4. In order to intuitively show the protection of the lithium negative electrode by the inhibition of the shuttle effect, the lithium-sulfur battery at the end of the self-discharge test was disassembled, and the lithium negative electrode was taken out for field emission scanning electron microscopy (FSEM) testing. The results are shown in Figure 5 and Figure 6 .

[0075] Depend on Figure 5 The results show that after the self-discharge test of the lithium-sulfur battery assembled using the gel electrolyte prepared in Example 2, the microscopic morphology of the surface of the lithium negative electrode presents a nodular structure with rounded edges, which is relatively flat overall.

[0076] Depend on Figure 6 The results show that after the self-discharge test of the lithium-sulfur battery assembled using the basic electrolyte prepared in Comparative Example 1, the microscopic morphology of the surface of the lithium negative electrode contains more moss-like and tree-like lithium dendrites.

[0077] The above results show that when the gel electrolyte of Example 2 is used in a lithium-sulfur battery, the dissolution of lithium polysulfide can be significantly reduced and the shuttle effect can be slowed down, thereby reducing the corrosion of lithium polysulfide on the metallic lithium negative electrode and having a protective effect on the metallic lithium negative electrode.

[0078] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.

Claims

1. A method for preparing a gel electrolyte for a lithium-sulfur battery, characterized in that: The following steps are involved: S1, adding lithium salt to an ether solvent, stirring and mixing, to obtain a mixed material A; Wherein, the ether solvent is a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether; the lithium salt includes lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate; S2, adding leucine as an initiator to the mixed material A, stirring the mixture at room temperature, and letting it stand to obtain a gel electrolyte for a lithium-sulfur battery; In step S2, the stirring reaction time is 3 to 8 hours, and the standing time is 8 to 12 hours; The amount of leucine added is 1.5-4.5wt% of the total mass of the mixed material A; In the mixed solvent, the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:(0.5-1); In the mixed material A, the molar concentration of the lithium bis(trifluoromethanesulfonyl)imide is 0.5-2.0 mol / L, and the mass concentration of the lithium nitrate is 1-10 wt %.

2. A gel electrolyte for lithium-sulfur battery prepared by the preparation method as claimed in claim 1.

3. A lithium-sulfur battery, characterized in that: The invention comprises the gel electrolyte for lithium-sulfur battery as claimed in claim 2.

Citation Information

Patent Citations

  • Gelling system containing cross-linking agent and preparation method and application thereof

    CN111106382A

  • Lithium metal battery electrolyte containing amino acid additive and preparation method thereof

    CN114373988A